Antisickling effect of chrysin is associated with modulation of oxygenated and deoxygenated haemoglobin via alteration of functional chemistry and metabolic pathways of human sickle erythrocytes - Nwankwo, H.C.; Idowu, A.A.; Muhammad, A. (Sage, 2021)
Sickle cell disease (SCD) treatment and management remain a challenging puzzle especially among developing Nations. Chrysin’s sickling-suppressive properties in human sickle (SS) erythrocytes in addition to its effect on AA-genotype erythrocytes were evaluated. Sickling was induced (76%) with 2% sodium metabisulphite at 3 h. Chrysin prevented (81.19%) the sickling and reversed same (84.63%) with strong IC50s (0.0257 mM and 0.00275 mM, respectively). The levels of oxygenated haemoglobin in the two groups (before and after induction approaches) were similar but significantly (P < 0.05) higher than that of SS erythrocytes (the ‘induced’ control), with chrysin-treated AA-genotype showing no effects relative to the untreated. The level of deoxygenated haemoglobin in the ‘induced’ control group was significantly (P < 0.05) higher than those of the chrysin-treated SS erythrocytes. Normal and chrysin-untreated erythrocytes (AA-untreated) were significantly more resistant to osmotic fragility than the SS-untreated. However, treatment with chrysin significantly reduced the osmotic fragility of the cells relative to the untreated cells. Furthermore, chrysin treatment significantly lowers the high level of 2,3-diphosphoglycerate (2,3-DPG) observed in the sickle erythrocytes, with no effects on AA-genotype erythrocytes. Based on functional chemistry, chrysin treatment alters the functional groups in favour of its antisickling effects judging from the observed bends and shifts. From metabolomics analysis, it was observed that chrysin treatment favors fatty acid alkyl monoesters (FAMEs) production with concomitant shutting down-effects on selenocompound metabolism. Thus, sickling-suppressive effects of chrysin could potentially be associated with modulation of oxygenated and deoxygenated haemoglobin via alteration of human sickle erythrocyte’s functional chemistry and metabolic pathways implicated in SCD crisis
Keywords: Sickling; chrysin; effects; haemoglobin; modulation; metabolomics; A.D. Wazir; Y.S. Abubakar; Ahmadu Bello University; ACENTDFB; ACE: Neglected Tropical Diseases and Forensic Biotechnology